How Technological Innovation Mediates between Strategic CSR and SMES Performance in Manufacturing Sector: Evidence from Malaysian Manufacturing Sector - Mary Olufunke , Adedokun; Danial Aslam, Hassan (International Journal of Psychosocial Rehabilitation, 2020)
Corporate social responsibility (CSR) is not only important for large firms; it is equally important for small and medium enterprises. As small and medium enterprises (SMEs) are taking much pressure from the buyer for successful implementation of strategic CSR practices. However, the main objective of the study is to investigate the mediating role of technological innovation between strategic CSR and SME performance in Malaysia to make sure of the effective implementation of strategic CSR practices, which can enhance the SMEs performance. The study has distributed the 500 questionnaires among manufacturing SME respondents and collected the valid 200 questionnaires for further analysis. The PLS-SEM technique has been employed to evaluate the data. The study revealed the positive link between strategic CSR and SME performance. Furthermore, the study also found the mediating role of technological innovation between strategic CSR and SME performance. In respect of implications, the current study suggested that the owner/managers of SMEs need to work on CSR practices; these practices can improve technological innovation, as technological innovation is highly important for higher SME performance.